Case report: Primary pericardial angiosarcoma, a rare cause of cardiac tamponade - Kong, Ling-Yun; Cui, Xiao-Zheng; Xiang, Wei; Wang, Xiu-Juan; Liu, Fang (Frontiers in Cardiovascular Medicine, 2024)
Primary pericardial angiosarcoma is a rare malignancy of the pericardium with variable clinical features and imaging characteristics. Herein, we report a case of histopathologically confirmed pericardial angiosarcoma in a 66-year-old man. The patient developed cardiac tamponade in a short time period. The transthoracic echocardiography showed the presence of multiple irregular echodensities, heterogeneous in echogenicity, encasing the apex of both ventricles in the pericardial space, initially misinterpreted as pericardial effusion. The patient died of cardiogenic shock despite undergoing a surgical pericardiectomy. Pericardial angiosarcoma can manifest as a mass obliterating the pericardial sac, rather than the typical pericardial effusion observed on echocardiography. Multimodality imaging studies aid in diagnosing primary pericardial angiosarcoma, but the final diagnosis relies on tissue histopathology.